Տ. Յակոբ քհնյ. Խաչվանքեանի կեանքը եւ գործունէութիւնը. ըստ իր անտիպ յուշագրութեան - Մելիքյան, Արեւիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлены учеба, а также педагогическая, духовная деятельность иерея Акопа Хачванкяна (по материалам его мемуаров). Подчеркнута важность его учебы в духовной семинарии Геворгян, затронута его педагогическая деятельность. Он преподавал в школах Пресвятой Богородицы (Сурб Аствацацин), Сааканушян, Св. Гриригорий Просветитель, Св. Всеспасителя в Александраполе, а также в школах для юнощей (Нор Баязет) и девиц (Моздок). С 7 апреля 1902 г. был священнослужителем части армянского общества Моздока. В статье особенно говорится о той большой роли, которую он сыграл в годы Первой мировой войны. Будучи членом Александропольского филиала Комитета братской помощи Эчмиадзина, отец Акоп вместе со своими помощниками заботился о беженцах: открывал приюты-общежития, поставлял еду и одежду, организовывал лечение больных, обращал внимание на санитарное состояние. В статье также говорится о событиях 1918 года, вдохновляющих выступлениях иерея Акопа Хачванкяна и Арама Манукяна в преддверии героической Сардарапатской битвы. The article aims to present Fr. Hakob Khachvankyan’s educational, pedagogical and ecclesiastical activities based on his memoirs. The article highlights the importance of Fr. Hakob Khachvankyan’s years of study at the Gevorkian Theological Seminary. Reference was made to his pedagogical activity. He used to teach at Holy Mother of God school in Alexandropol, Sahakanushyan girls’ school, Holy Savior, St. Lusavorich Khrimyan schools, boys’ and girls’ schools in Nor Bayazet, as well as at school of Mozdok. On April 7, 1902, he became the pastor of a part of the Armenian community of Mozdok. The article focuses mainly on the great role he played during World War I. As a member of the Alexandropol branch of the Holy Etchmiadzin Fraternal Relief Committee, Fr. Hakob Khachvankyan and his assistants cared for refugees. He opened orphanage-dormitories, provided food and clothing, organized treatment of the sick, and paid attention to sanitary conditions. The article also refers to the events of 1918, the inspiring speeches of Khachvankyan and Aram Manukyan on the eve of the heroic Battle of Sardarapat.
Keywords: Հայոց եկեղեցւոյ պատմութիւն